Impacts of land cover and management change on top-of-canopy and below-canopy temperatures in Southeastern Kenya - Abera, T.; Heiskanen, J.; Maeda, E.; Odongo, Vincent O.; Pellikka, P. (Elsevier, 2023)
Impacts of land cover conversion have been studied well from the top-of-canopy level using satellite observations. Yet, the warming or cooling impacts of land cover and management change (LCMC) from below-canopy level remain less explored. Here, we studied the below-canopy temperature change from field to landscape level across multiple LCMC in southeastern Kenya. To study this, in situ microclimate sensors, satellite observations, and high-resolution below-canopy temperature modelling approaches were used. Our results show that from field to landscape scale, forest to cropland conversion, followed by thicket to cropland change, generate higher surface temperature warming than other conversion types. At field scale, tree loss increases the mean soil temperature (measured at 6 cm below ground) more than the mean below-canopy surface temperature but its impact on the diurnal temperature range was higher on surface temperature than soil temperature in both forest to cropland and thicket to cropland/grassland conversions. At landscape scale, compared with top-of-canopy land surface temperature warming, which was estimated at Landsat overpass time (∼10:30 a.m.), forest to cropland conversion generates ∼3 °C higher below-canopy surface temperature warming. Land management change, through fencing of wildlife conservation areas and limiting mobility of mega browsers, can have an impact on woody cover and induce more below-canopy surface temperature warming than top-of-canopy in comparison with non-conservancy areas. These results indicate that human induced land changes can generate more below-canopy warming than inferred from top-of-canopy satellite observations. Together, the results highlight the importance of considering the climatic impacts of LCMC from both top-of-canopy and below-canopy level for effective mitigation of anthropogenic warming from land surface changes.